Pengaruh Profitabilitas, dan Kebijakan Hutang terhadap Nilai Perusahaan pada PT. Kalbe Farma Tbk Periode 2012-2022 - Bima Reresa Sukron Kausar Muhorif; Ahmad Idris; Rafikhein Novia Ayuanti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of profitability and debt policy on Company Value at PT Kalbe Farma Tbk for the period 2012-2022. This type of research is quantitative research. The data for this study were obtained through secondary data. Based on the total sampling method, the total research sample was 44 in the form of financial reports of PT Kalbe Farma Tbk. The analysis techniques used were classical assumption tests, multiple linear regression analysis, hypothesis tests and determinant coefficient tests. The results of the study showed that the partial t-test results of the profitability variable had a negative and insignificant effect on company value, Debt Policy had a positive and significant effect on company value. The results of the simultaneous F-test of the profitability variable and debt policy had a positive and significant effect on stock prices.